H-BN ceramic with adjustable thermal expansion as well as preparation method and application of h-BN ceramic
By using boron azine polymer as a sintering aid and expansion phase in hexagonal boron nitride ceramics, the adjustability of the thermal expansion performance of h-BN ceramics is achieved, solving the problem of ceramic densification and thermal expansion coefficient matching, and improving its mechanical and electrical properties.
Patent Information
- Application Number
- CN202411911766.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing hexagonal boron nitride ceramics are difficult to densify during the sintering process, resulting in poor mechanical properties. At the same time, their thermal expansion coefficient does not match the adjacent materials, resulting in thermal stress and deformation problems.
Boron azine polymer is used as the expansion phase and sintering aid, and then mixed with h-BN powder and heat-pressed sintering is carried out. By adjusting the mass ratio of boron azine polymer to h-BN powder, the thermal expansion coefficient of h-BN ceramic is adjusted.
The adjustability of the thermal expansion performance of h-BN ceramics is achieved, and the thermal expansion coefficient is adjustable in the range of 4~14.6×10-6/K, which maintains good mechanical properties, dielectric properties and high temperature resistance, and solves the problem of mismatch in the thermal expansion coefficient.
Smart Images

Figure CN119684011A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of boron nitride ceramic materials, and in particular to h-BN ceramics with adjustable thermal expansion, and a preparation method and application thereof. Background Art
[0002] Hexagonal boron nitride ceramics (h-BN) have excellent comprehensive properties such as high temperature resistance, high thermal conductivity, corrosion resistance, low dielectric constant, strong mechanical properties and stable chemical properties, and have been widely used in the fields of chemical industry, aerospace, etc. At present, the commonly used preparation methods of h-BN ceramics mainly include pressureless sintering (PLS), hot pressing sintering (HP), spark plasma sintering (SPS), and hot isostatic pressing sintering. On the one hand, there are certain problems in the different preparation processes of existing hexagonal boron nitride ceramics, such as CN104193341A (which discloses a method for preparing high-purity hexagonal boron nitride by pressureless sintering), using h-BN powder as raw material, pre-pressing and forming, first pre-sintering in a muffle furnace under air atmosphere, and then pressureless sintering in a tubular furnace under nitrogen atmosphere, the density of high-purity hexagonal boron nitride obtained by this method is only 59.03% of the theoretical density at most, and the three-point bending strength at room temperature is only 59.7MPa. This is because h-BN has a hexagonal layered structure, in which N atoms and B atoms in the layer are bonded by strong covalent bonds, arranged alternately to form a six-membered ring, and the layers are bonded by van der Waals forces. The covalent bond and the special lamellar structure lead to more pores between the grains and a low self-diffusion coefficient. h-BN is difficult to sinter and densify, resulting in poor mechanical properties. In order to improve its sintering activity, traditional sintering methods often require the addition of sintering aids, such as B2O3, Al2O3, Y2O3, etc., and these sintering aids melt into a liquid phase at high temperature and have a higher dielectric constant than BN ceramics, which will lead to a decrease in the high-temperature mechanical and electrical properties of h-BN ceramics, limiting the application of h-BN.
[0003] On the other hand, the existing preparation technology cannot solve the problem of thermal expansion coefficient mismatch between h-BN ceramics and its adjacent materials in the application of h-BN ceramics. In the application scenario of h-BN ceramics, there is uneven temperature or inconsistent thermal expansion coefficient between h-BN ceramics and adjacent materials, which will cause thermal stress and deformation problems. At present, there is a lack of research on active design and adjustment of the thermal expansion coefficient of h-BN ceramics in order to solve the problem of thermal expansion coefficient mismatch between h-BN ceramics and their adjacent materials in the application of h-BN ceramics. In the current preparation of h-BN ceramics, researchers can passively change the thermal expansion coefficient of h-BN ceramics by adding different sintering aids. For example, Zhou Tian et al. (Zhou Tian et.al.Ceramics International, 2023, 49(8), 12481–12490.) added Al2O3 and Y2O3 to h-BN powder to obtain a thermal expansion coefficient ranging from 2.87-7.3×10 -6 / K h-BN ceramics; Ning Liao et al. (Ning Liao et al.al.Materials Science and Engineering:A, 2019, 767:138443.) added nano-Al2O3, ZrO2 and SiC as sintering aids to h-BN powder to obtain h-BN ceramics with a thermal expansion coefficient ranging from 2.1 to 3.82×10 -6 / K. On the one hand, the above additives have limited ability to adjust the thermal expansion of h-BN ceramics, and it is difficult to achieve an adjustable thermal expansion coefficient of 10×10 -6 / K breakthrough; in addition, the introduction of oxide additives will cause negative effects as mentioned above, limiting the application of h-BN ceramics. Summary of the invention
[0004] In view of the above shortcomings, the present invention provides a method for preparing h-BN ceramics with adjustable thermal expansion, which realizes adjustable thermal expansion performance of h-BN ceramics, is beneficial to the application of h-BN ceramics, and overcomes the problems of traditional sintering aids SiO2, Al2O3, and Y2O3 leading to the decrease of high-temperature mechanical properties and electrical properties of h-BN ceramics. The specific technical scheme is as follows:
[0005] A method for preparing h-BN ceramics with adjustable thermal expansion comprises: using a borazine polymer as an expansion phase and a sintering aid, mixing the borazine polymer with h-BN powder, and then hot pressing and sintering to obtain the h-BN ceramics with adjustable thermal expansion.
[0006] The present invention adopts borazine polymer as a sintering aid, which can effectively promote the low-temperature preparation of h-BN ceramics without introducing a second phase, ensuring that the h-BN ceramics have good mechanical properties, dielectric properties and high-temperature resistance. The thermal expansion coefficient of the h-BN ceramics is adjusted by adjusting the mass ratio of the borazine polymer and the h-BN powder. The adjustment range of the thermal expansion coefficient of the h-BN ceramics is 4 to 14.6×10 -6 / K.
[0007] Preferably, in the above-mentioned method for preparing h-BN ceramics with adjustable thermal expansion, the mass ratio of the borazine polymer to the h-BN powder is 20-85%:15-80%.
[0008] Preferably, the method for preparing the h-BN ceramic with adjustable thermal expansion comprises the following steps:
[0009] (1) adding a borazine polymer and h-BN powder into kerosene and n-hexane respectively to obtain suspension 1 and suspension 2; the suspension 1 and the suspension 2 are mixed, ball-milled, and then spray-dried to obtain a raw material powder;
[0010] (2) pressing the raw material powder obtained in step (1) to obtain a green body;
[0011] (3) The green body obtained in step (2) is subjected to pressure sintering, and the sintering process is: pre-sintering at 500-800°C in a protective atmosphere, and then secondary sintering at 1000-1500°C after cooling, and the pressure of the two sinterings is 25-50MPa, to obtain h-BN ceramics with adjustable thermal expansion. The method of hot pressing sintering in stages can effectively reduce the grain size of h-BN ceramics and avoid the problems of poor densification and decreased mechanical properties caused by large grains; the secondary sintering temperature below 1000°C has no sintering effect, and the effect of suppressing grain size is weakened when it is higher than 1500°C.
[0012] Preferably, in the above-mentioned method for preparing h-BN ceramics with adjustable thermal expansion, the borazine polymer is obtained by curing liquid borazine in a sealed container at a temperature of 50 to 200° C. and keeping the temperature for 72 to 120 hours.
[0013] Preferably, in the method for preparing the h-BN ceramic with adjustable thermal expansion, the heating rate is 5 to 10° C. / min.
[0014] Preferably, the above-mentioned method for preparing h-BN ceramics with adjustable thermal expansion is characterized in that, in step (1), the solid content in suspension 1 and suspension 2 is 45-55%, and the ball milling process parameters are: rotation speed is 200-300 rpm, and time is 24-48 h.
[0015] Preferably, in the above-mentioned method for preparing h-BN ceramics with adjustable thermal expansion, in the step (2), the pressing pressure is 10 to 20 MPa.
[0016] Preferably, in the above-mentioned method for preparing h-BN ceramics with adjustable thermal expansion, in the step (3), the sintering heating rate is 5 to 10° C. / min, and the sintering heat preservation and pressure holding time is 1 to 4 hours.
[0017] Preferably, in the above-mentioned method for preparing h-BN ceramics with adjustable thermal expansion, the spray drying is: using a nitrogen spray drying system to maintain the inlet and outlet temperatures at 150°C.
[0018] On the other hand, the present invention further provides a h-BN ceramic with adjustable thermal expansion, wherein the h-BN ceramic with adjustable thermal expansion is prepared by the above-mentioned preparation method.
[0019] On the other hand, the present invention also provides the use of the above-mentioned h-BN ceramics with adjustable thermal expansion in the preparation of high-speed aircraft antenna cover windows, side sealing plates for twin-roll thin strip continuous casting, high-temperature melting crucibles and clamping components and / or Hall thruster channels.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The thermal expansion performance of the hexagonal boron nitride ceramic (h-BN ceramic) of the present invention can be adjusted, and the thermal expansion coefficient is 4 to 14.6×10 -6 / K range is adjustable, and it has good mechanical properties, dielectric properties and high temperature resistance. It can be used in microwave tube energy transmission windows / support rods, wave-transmitting antenna covers / window materials and other fields.
[0022] 2. In the preparation method of h-BN ceramics with adjustable thermal expansion of the present invention, borazine polymer is used as the expansion phase source and h-BN powder is used as the matrix phase source. By changing the ratio of borazine polymer to h-BN powder, the preparation of h-BN ceramics with adjustable thermal expansion properties is achieved, which solves the problem of mismatch in thermal expansion coefficients between h-BN ceramics and adjacent materials when used as a material for making wave-transmitting antenna covers or wave-transmitting antenna windows.
[0023] 3. In the preparation method of h-BN ceramics with adjustable thermal expansion of the present invention, borazine polymer is used as a sintering aid. Its unique NH and BH active bonds can effectively promote the sintering of h-BN ceramics and reduce the sintering temperature; and compared with traditional sintering aids such as SiO2, Al2O3, Y2O3, etc., the introduction of borazine polymer will not bring about a decrease in the dielectric and high temperature resistance of h-BN ceramics.
[0024] 4. In the preparation method of the h-BN ceramic with adjustable thermal expansion of the present invention, the stepwise hot pressing sintering method is adopted, which can effectively reduce the grain size of the h-BN ceramic compared with the one-step hot pressing sintering, and avoid the problems of poor densification effect and decreased mechanical properties caused by large grains. The production cost is low and the production efficiency is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 This is a physical picture of the h-BN ceramic of Example 1;
[0027] Figure 2 is the X-ray diffraction pattern of the h-BN ceramic of Example 1;
[0028] Figure 3 This is a fracture microscopic morphology of the h-BN ceramic of Example 1. DETAILED DESCRIPTION
[0029] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention, etc. can be purchased from the market or can be prepared by existing methods.
[0030] Example 1
[0031] This embodiment provides an h-BN ceramic with adjustable thermal expansion coefficient, which includes an expansion phase and a matrix phase. The expansion phase is derived from a borazine polymer, and the matrix phase is derived from h-BN powder, wherein the mass fraction of the borazine polymer is 80% and the mass fraction of the h-BN powder is 20%.
[0032] This embodiment also provides a method for preparing the h-BN ceramic, comprising the following steps:
[0033] (1) The liquid borazine is heated to 200°C at 5°C / min in a sealed container and kept at this temperature for 80 hours to solidify and obtain a borazine polymer.
[0034] (2) adding the borazine polymer and h-BN powder to kerosene and n-hexane at a mass ratio of 80%:20% to obtain suspensions 1 and 2, wherein the solid content of suspensions 1 and 2 is 50%; mixing the borazine polymer and h-BN powder to prepare suspensions is beneficial to improving the dispersion effect;
[0035] (3) Suspension 1 and suspension 2 were mixed, ball-milled at 200 r / min for 48 h to fully mix and refine, and then spray-dried using a nitrogen spray drying system while maintaining the inlet and outlet temperatures at 150° C. to obtain a raw material powder.
[0036] (4) The powder obtained by ball milling is pressed into a mold at a pressure of 10 MPa to obtain a green body.
[0037] (5) The green body is pre-sintered in a nitrogen atmosphere at a sintering pressure of 30 MPa, a sintering temperature of 600°C, a heating rate of 10°C / min, and a heat and pressure holding time of 2 h; after cooling, the green body is heated to 1200°C for secondary sintering at a heating rate of 10°C / min, a pressure of 30 MPa, and a sintering time of 3 h to obtain the h-BN ceramic.
[0038] Figure 1 This is a photo of the h-BN ceramic prepared in this example. Figure 2 is the X-ray diffraction pattern, Figure 3The microstructure of the h-BN ceramic prepared in this example is a uniform h-BN phase with uniform grain size. The mechanical properties and thermal expansion coefficient of the h-BN ceramic prepared in this example were tested. The flexural strength was 104.9 MPa and the thermal expansion coefficient was 13.2×10 -6 / K, the test temperature range is 50~450℃.
[0039] Example 2
[0040] This embodiment provides an h-BN ceramic with adjustable thermal expansion coefficient, which includes an expansion phase and a matrix phase. The expansion phase is derived from a borazine polymer, and the matrix phase is derived from h-BN powder, wherein the mass fraction of the borazine polymer is 50%, and the mass fraction of the h-BN powder is 50%.
[0041] This embodiment also provides a method for preparing the h-BN ceramic, comprising the following steps:
[0042] (1) The liquid borazine is heated to 200°C at 5°C / min in a sealed container and kept at this temperature for 80 hours to solidify and obtain a borazine polymer.
[0043] (2) adding the borazine polymer and h-BN powder to kerosene and n-hexane at a mass ratio of 50%:50% to obtain suspension 1 and suspension 2, wherein the solid content of suspension 1 and suspension 2 is 50%; mixing the borazine polymer and h-BN powder separately to form suspensions is beneficial to improving the dispersion effect;
[0044] (3) Suspension 1 and suspension 2 were mixed, ball-milled at 200 r / min for 48 h to fully mix and refine, and then spray-dried using a nitrogen spray drying system while maintaining the inlet and outlet temperatures at 150° C. to obtain a raw material powder.
[0045] (4) The powder obtained by ball milling is pressed into a mold at a pressure of 10 MPa to obtain a green body.
[0046] (5) The green body is pre-sintered in a nitrogen atmosphere at a sintering pressure of 30 MPa, a sintering temperature of 600°C, a heating rate of 10°C / min, and a heat and pressure holding time of 2 h; after cooling, the green body is heated to 1200°C for secondary sintering at a heating rate of 10°C / min, a pressure of 30 MPa, and a sintering time of 3 h to obtain the h-BN ceramic.
[0047] The h-BN ceramic in this embodiment has a bending strength of 136.6 MPa and a thermal expansion coefficient of 8.97×10 -6 / K.
[0048] Example 3
[0049] This embodiment provides an h-BN ceramic with adjustable thermal expansion coefficient, which includes an expansion phase and a matrix phase. The expansion phase is derived from a borazine polymer, and the matrix phase is derived from h-BN powder, wherein the mass fraction of the borazine polymer is 20% and the mass fraction of the h-BN powder is 80%.
[0050] This embodiment also provides a method for preparing the h-BN ceramic, comprising the following steps:
[0051] (1) The liquid borazine is heated to 200°C at 5°C / min in a sealed container and kept at this temperature for 80 hours to solidify and obtain a borazine polymer.
[0052] (2) adding the borazine polymer and h-BN powder to kerosene and n-hexane at a mass ratio of 20%:80% to obtain suspensions 1 and 2, wherein the solid content of suspensions 1 and 2 is 50%; mixing the borazine polymer and h-BN powder to prepare suspensions is beneficial to improving the dispersion effect;
[0053] (3) Suspension 1 and suspension 2 were mixed, ball-milled at 200 r / min for 48 h to fully mix and refine, and then spray-dried using a nitrogen spray drying system while maintaining the inlet and outlet temperatures at 150° C. to obtain a raw material powder.
[0054] (4) The powder obtained by ball milling is pressed into a shape at a pressure of 20 MPa to obtain a green body.
[0055] (5) The green body is pre-sintered in a nitrogen atmosphere at a sintering pressure of 30 MPa, a sintering temperature of 700°C, a heating rate of 10°C / min, and a heat and pressure holding time of 2 h; after cooling, the green body is heated to 1200°C for secondary sintering at a heating rate of 10°C / min, a pressure of 30 MPa, and a sintering time of 3 h to obtain the h-BN ceramic.
[0056] The h-BN ceramic in this embodiment has a bending strength of 111.5 MPa and a thermal expansion coefficient of 4.7×10 -6 / K.
[0057] Example 4
[0058] This embodiment provides an h-BN ceramic with adjustable thermal expansion coefficient, which includes an expansion phase and a matrix phase. The expansion phase is derived from a borazine polymer, and the matrix phase is derived from h-BN powder, wherein the mass fraction of the borazine polymer is 50%, and the mass fraction of the h-BN powder is 50%.
[0059] This embodiment also provides a method for preparing the h-BN ceramic, comprising the following steps:
[0060] (1) heating the liquid borazine in a sealed container to 200° C. at a rate of 5° C. / min and maintaining the temperature for 80 hours to solidify and obtain a borazine polymer;
[0061] (2) adding the borazine polymer and h-BN powder to kerosene and n-hexane at a mass ratio of 50%:50% to obtain suspension 1 and suspension 2, wherein the solid content of suspension 1 and suspension 2 is 50%; mixing the borazine polymer and h-BN powder separately to form suspensions is beneficial to improving the dispersion effect;
[0062] (3) Suspension 1 and suspension 2 were mixed, ball-milled at 200 r / min for 48 h to fully mix and refine, and then spray-dried using a nitrogen spray drying system while maintaining the inlet and outlet temperatures at 150° C. to obtain a raw material powder.
[0063] (4) The powder obtained by ball milling is pressed into a shape at a pressure of 20 MPa to obtain a green body.
[0064] (5) The green body is pre-sintered in a nitrogen atmosphere at a sintering pressure of 30 MPa, a sintering temperature of 700°C, a heating rate of 10°C / min, and a heat and pressure holding time of 2 h; after cooling, the green body is heated to 1000°C for secondary sintering at a heating rate of 10°C / min and a sintering time of 3 h to obtain the h-BN ceramic.
[0065] The h-BN ceramic in this embodiment has a bending strength of 98 MPa and a thermal expansion coefficient of 9.1×10 -6 / K.
[0066] Comparative Example
[0067] This comparative example provides h-BN ceramics obtained by direct hot pressing and sintering of pure h-BN powder, and the specific steps include:
[0068] S1: Add h-BN powder into n-hexane to prepare a suspension with a solid content of 50%;
[0069] S2: The suspension obtained in S1 was ball-milled at 200 r / min for 48 h to mix and refine, and then spray-dried using a nitrogen spray drying system while maintaining the inlet and outlet temperatures at 150°C to obtain a raw material powder;
[0070] S3: The powder obtained by ball milling is pressed into a mold at a pressure of 20 MPa to obtain a green body.
[0071] S4: Under N2 atmosphere, the sintering pressure is 30 MPa, and the green body is pre-sintered at a temperature of 700°C for 1 to 4 hours; after cooling, the temperature is raised to 1800°C for secondary sintering to obtain h-BN ceramics.
[0072] The thermal expansion coefficient of the h-BN ceramic in this comparative example is 1.5×10 -6 / K, flexural strength 20MPa.
[0073] Table 1 is a comparison of the properties of h-BN ceramics prepared in Examples 1 to 3 and the comparative example. From the data in the table, it can be seen that the present invention can adjust the thermal expansion properties of h-BN ceramics by adding borazine polymer as a sintering aid and expansion phase source, and has good mechanical properties and dielectric properties.
[0074] Table 1 Relevant properties of each example and comparative example
[0075]
[0076] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A method for preparing h-BN ceramics with adjustable thermal expansion, characterized in that: include: Borazine polymer is used as an expansion phase and a sintering aid, the borazine polymer is mixed with h-BN powder, and then hot-pressed and sintered to obtain h-BN ceramics with adjustable thermal expansion.
2. The method for preparing h-BN ceramics with adjustable thermal expansion according to claim 1, characterized in that: The mass ratio of the borazine polymer to the h-BN powder is 20-85%:15-80%.
3. The method for preparing h-BN ceramics with adjustable thermal expansion according to claim 1, characterized in that: The following steps are involved: (1) adding a borazine polymer and h-BN powder into kerosene and n-hexane respectively to obtain suspension 1 and suspension 2; the suspension 1 and the suspension 2 are mixed, ball-milled, and then spray-dried to obtain a raw material powder; (2) pressing the raw material powder obtained in step (1) to obtain a green body; (3) The green body obtained in step (2) is subjected to pressure sintering. The sintering process is as follows: pre-sintering is performed at 500-800° C. in a protective atmosphere, and then secondary sintering is performed at 1000-1500° C. after cooling. The pressure of both sintering processes is 25-50 MPa to obtain h-BN ceramics with adjustable thermal expansion.
4. The method for preparing h-BN ceramics with adjustable thermal expansion according to claim 3, characterized in that: The borazine polymer is obtained by heating liquid borazine to 50-200° C. in a sealed container and keeping the temperature for 72-120 hours to solidify the liquid.
5. The method for preparing h-BN ceramics with adjustable thermal expansion according to claim 3, characterized in that: In the step (1), the solid content of the suspension 1 and the suspension 2 is 45-55%, and the ball milling process parameters are: rotation speed is 200-300 rpm, and time is 24-48 hours.
6. The method for preparing h-BN ceramics with adjustable thermal expansion according to claim 3, characterized in that: In the step (2), the pressure of the pressing molding is 10 to 20 MPa.
7. The method for preparing h-BN ceramics with adjustable thermal expansion according to claim 3, characterized in that: In the step (3), the sintering heating rate is 5 to 10°C / min, and the heat preservation and pressure holding time of the two sinterings is 1 to 4 hours respectively.
8. The method for preparing h-BN ceramics with adjustable thermal expansion according to claim 4, characterized in that: The heating rate is 5-10°C / min.
9. A h-BN ceramic with adjustable thermal expansion, characterized in that: The h-BN ceramic with adjustable thermal expansion is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the h-BN ceramic with adjustable thermal expansion as claimed in claim 9 in the preparation of high-speed aircraft radome windows, side sealing plates for twin-roll thin strip continuous casting, high-temperature melting crucibles and clamping components and / or Hall thruster channels.
Citation Information
Patent Citations
Method for preparing high-purity hexagonal boron nitride ceramic by pressureless sintering
CN104193341A
Method for manufacturing high-density boron nitride ceramic
CN106588027A
Silicon nitride nanometer fiber reinforced boron nitride ceramic, and preparation method thereof
CN110330349A
Acid-catalyzed dehydrogenation of amine-boranes
US20060292068A1
Shaped body, especially a pressed or sintered body comprising boron nitride and method for introducing or producing boron nitride in a porous shaped body
WO2003027213A1